Childhood lung function is associated with adolescent-onset and persistent asthma - Hans Jacob L. Koefoed; Anhar Ullah; Jenny Hallberg; Simon Kebede Merid; Maura M. Kere; Lesley Lowe; Angela Simpson; Clare S. Murray; Ulrike Gehring; Roel Vermeulen; Inger Kull; Anna Bergström; et al. (ERJ Open Research)
Background Asthma is associated with impaired lung function; however, it is uncertain if a lower childhood lung function is associated with asthma onset and persistence during adolescence. The aims of the present study were to investigate the association between childhood lung function and onset and persistence of asthma during adolescence. Methods In the population-based BAMSE (Sweden), PIAMA (Netherlands) and MAAS (UK) birth cohorts, we analysed the association of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC and forced expiratory volume at 75% of FVC at age 8 years with asthma onset and persistence in adolescence (age 12–16 years) using cohort-specific logistic regression analysis followed by meta-analysis. Results In the BAMSE, PIAMA and MAAS cohorts, asthma incidence in adolescence was 6.1% (112/1824), 3.4% (36/1050) and 5.0% (39/779), respectively. Persistent asthma from childhood to adolescence was observed in 8.2%, 6.4% and 7.7% of all subjects within the respective cohorts. A higher FEV1 % predicted and FEV1/FVC at age 8 years was associated with a lower odds for adolescent-onset asthma: OR 0.98 (95% CI 0.97–1.00) and 0.97 (0.94–0.99). These associations remained significant also when restricting the analyses to subjects with no wheezing or asthma treatment in childhood. A higher FEV1/FVC at age 8 years was associated with a lower odds for asthma persistence in adolescence (0.96 (0.93–0.99)). Sex by lung function interaction analysis was not significant. Conclusions A higher lung function at school age was associated with a lower risk of adolescent-onset asthma, predominantly in males. This indicates that a lower lung function in childhood may precede and or potentially contribute to asthma incidence and persistence.